Pemanfaatan Teknologi Sistem Informasi untuk Meningkatkan Penjualan Hasil Produk UMKM Logam di Kota Pasuruan - Mochamad Mas'ud (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2017)
The Metal Crafters in Pasuruan City who are members of the Indonesian Prosperous (PASINDO) oversees about 300 UMKM of metal. Partners taken by machining and casting groups and packing groups. Metal Craftsman Company manages the management manually, if there is ordering according to job order recorded in big book and finance is not set. Factors in focusing assistance to metal craftsmen under the auspices of Pasindo is knowledge of management information technology and marketing to increase sales. Output targets implemented include conducting financial management and marketing training, operationalizing application systems, entry training and data updating in databases, as well as providing order management training through e-commerce application systems. Method offered approach Metal business unit as seller and buyer based on information technology include: Observation on business partners, designing and making e- commerce application system, and training to Partners. Retail data for 14 months before using a Web-based sales application on a sample of 30 products generated a net profit of Rp. 5,120,000. Sales for 2 months after using the Web application generated a net profit of Rp. 4,356,000. It experienced an increase in profit of Rp. 1,812,286 every month after using a Web-based sales app (E-Commerce).